Is Penicillin Plus Gentamicin Synergistic against Clinical Group B Streptococcus isolates?: An In vitro Study - Ruppen, Corinne; Lupo, Agnese; Decosterd, Laurent; Sendi, Parham (Frontiers in microbiology, 2016)
Group B (GBS) is increasingly causing invasive infections in non-pregnant adults. Elderly patients and those with comorbidities are at increased risk. On the basis of previous studies focusing on neonatal infections, penicillin plus gentamicin is recommended for infective endocarditis (IE) and periprosthetic joint infections (PJI) in adults. The purpose of this study was to investigate whether a synergism with penicillin and gentamicin is present in GBS isolates that caused IE and PJI. We used 5 GBS isolates, two clinical strains and three control strains, including one displaying high-level gentamicin resistance (HLGR). The results from the checkerboard and time-kill assays (TKAs) were compared. For TKAs, antibiotic concentrations for penicillin were 0.048 and 0.2 mg/L, and for gentamicin 4 mg/L or 12.5 mg/L. In the checkerboard assay, the median fractional inhibitory concentration indices (FICIs) of all isolates indicated indifference. TKAs for all isolates failed to demonstrate synergism with penicillin 0.048 or 0.2 mg/L, irrespective of gentamicin concentrations used. Rapid killing was seen with penicillin 0.048 mg/L plus either 4 mg/L or 12.5 mg/L gentamicin, from 2 h up to 8 h hours after antibiotic exposure. TKAs with penicillin 0.2 mg/L decreased the starting inoculum below the limit of quantification within 4-6 h, irrespective of the addition of gentamicin. Fast killing was seen with penicillin 0.2 mg/L plus 12.5 mg/L gentamicin within the first 2 h. Our results indicate that the addition of gentamicin to penicillin contributes to faster killing at low penicillin concentrations, but only within the first few hours. Twenty-four hours after antibiotic exposure, PEN alone was bactericidal and synergism was not seen.